Interactions of Mineral Dust with Clouds, Sea Surface Temperature, and Climate Modes of Variability - DeFlorio, Michael J. (eScholarship, University of California, 2015)
Global climate models (GCMs) are a vital tool for ensuring the prosperity and security of modern society. They allow scientists to understand complex interactions between the air, ocean, and land, and are used by policymakers to project future changes in climate on regional and global scales. The previous generation of GCMs, represented by CMIP3 models, are shown to be deficient in their representation of precipitation over the western United States, a region that depends critically on wintertime orographically enhanced precipitation for drinking water. In addition, aerosol-cloud interactions were prescribed in CMIP3 models, which decreased the value of their representation of global aerosol, cloud, and precipitation features. This has potentially large impacts on global radiation budgets, since aerosol-cloud interactions affect the spatial extent and magnitude of clouds and precipitation. The newest suite of GCMs, the Coupled Model Intercomparison Project Phase 5 (CMIP5) models, includes state-of-the-art parameterizations of small-scale features such as aerosols, clouds, and precipitation, and is widely used by the scientific community to learn more about the climate system. The Community Earth System Model (CESM), in conjunction with observations, provides several simulations to investigate the role of aerosols, clouds, and precipitation in the climate system and how they interact with larger modes of climate variability. We show that CESM produces a realistic spatial distribution of precipitation extremes over the western U.S., and that teleconnected signals of ENSO and the Pacific Decadal Oscillation to large-scale circulation patterns and precipitation over the western U.S. are improved when compared to CCSM3. We also discover a new semi-direct effect between dust and stratocumulus clouds over the subtropical North Atlantic, whereby boundary layer inversion strength increases during the most dusty summers due to shortwave absorption of dust above the planetary boundary layer. We find that ENSO exerts a control on North African dust transport during the summer, and CESM suggests that there is strong multi-decadal variability in the strength of the ENSO-dust relationship. Finally, we compare interactive and prescribed aerosol CESM simulations to demonstrate the importance of dust in increasing tropical Atlantic SST variability, and expose deficiencies in CESM's simulation of the Atlantic Meridional Mode